EDUCATION OF PRIMARY SCHOOL PUPIL ON THE BASIS OF UKRAINIAN FOLKLORE - Иовхимчук, Наталья; Здиховська, Татьяна (SWorldJournal, 2021)
The article considers the category of Ukrainian folklore, which remains a powerful factor in the education of the younger generation. The theme of love for the homeland sounds in all genres - from large epic works to short and accurate. The simplest moral